Us and them: Privileged emotions of Cape Town's urban water crisis. Issue 141 (May 2023) - Savelli, Elisa
Highlights: Emotions are not hardwired reactions of the brain but a product of subjectivities and the power dynamics they internalize. Privileged emotional geographies reveal the power through which elites maintain their privilege and with it, their unjust control and unsustainable use of water resources. Power laden emotions become imprinted in space as they materially and discursively reshape surrounding people and places. Privilege emotions risk shifting a water crisis towards the future when they restore the uneven and unsustainable conditions that had produced the water crisis in the first place. A focus on privileged emotions can advance political ecology's understandings of urban water crises. Abstract: Political ecology has already engaged with emotions in order to reveal the intimate, unconscious and unexplored power dynamics which characterise patterns of water use and control. Similar explorations have mostly focused on the emotional struggles of structurally disadvantaged people rather than on the emotions of those with privilege: the elite. This oversight becomes problematic when it conceals disproportionate shares of power and the implications that such power has on the sustainable use and just distribution of water resources. The 2018 water crisis which affected Cape Town's metropolitan area constitutes the empirical context of this paper, which sets out to address the aforementioned research gap. Focusing on the elite's emotional responses to Cape Town's drought and subsequent water crisis, this paper seeks to advance political ecology's understanding of urban water crises by retracing the emotional geography of Cape Town's most privileged urban dwellers. In particular, this work leverages the concept of subjectivity to explain the way emotions are constructed and come to materially and discursively reproduce historical power dynamics. These findings reveal that fear, anger, and a sense of pride felt by wealthier Capetonians results from and perpetuates the privileged conditions of those elite. Rooted in colonial and apartheid past, Capetonians' privileged emotions end up perpetuating the main causes of the water crisis and eventually excluding the most disadvantaged inhabitants from future use and control of water resources. Ultimately, by connecting with privileged emotions, it is possible to challenge certain subjectivities and create space for more just and sustainable urban-water imaginaries.